THE IMPLEMENTATION OF ON-GOING ASSESSMENT IN AN EYL CLASS - Kustina , Amy (2014)
A shifting process from School-Based Curriculum that has been implemented since 2006 into Curriculum 2013 gave some impacts into the way assessing students, especially for young learners. This shifting urges a need of implementing an on-going assessment as a way to measure students' ability rather than using traditional paper-pencil testing. This study examined the presence of learning support provided by on-going assessment and also challenges in implementing on-going assessment among 31 of third grade students in a private elementary school in Bandung. A qualitative analysis found that on-going assessments for EYL which were implemented through picture-cued description, information exchange, matching activity and written product provided support for learning. The supports were in the forms of repetition and opportunity to say the words in model of language use during the learning, students' participations which indicated the building process of intrinsic and extrinsic motivation and the occurrence of student's autonomy and responsibility in the development for their further learning. The study also found that size of the class and classroom management became the main challenges in implementing on-going assessment in the classroom. Therefore, providing more varied materials and forms of assessments were recommended for betterment in the future research. Key words: On-going assessment, English for Young Learners (EYL).